Proteins functionalization: a strategy that boost the performance of these macromolecules for innovative pharmaceutical and food developments - QUINTERO QUIROZ, Julián; ROJAS CAMARGO, Jhon Jairo (Vitae, 2018)
Proteins are macromolecules exhibiting amphiphilic properties, good biocompatibility, biodegradability, high nutritional value, and show strong interactions with several types of active compounds via hydrogen bonding and electrostatic interactions. These plant or animal-derived macromolecules differ in their molecular size depending on the number of amino acids present in their structure, which in turn, are linked by peptide bonds between the carbonyl (-CO-) and amino groups (-NH).